Studi Arsitektural dan Sejarah Peninggalan Kesultanan Langkat di Gebang - Ningsih, Sri; Ritonga, Sakti; Faturrahman, Muslih (Local History & Heritage, 2024)
This study explores the historical heritage of the Langkat Sultanate, specifically focusing on mosques and tombs. The documentation and preservation of historical relics are crucial to maintaining their value as part of the nation's identity. The research employs a historical approach using methods such as heuristics, source criticism, interpretation, architectural analysis, and historiography. Data were collected through interviews, direct observation at the research site, and literature studies. The findings indicate that Gebang played a significant role in the history of the Langkat Sultanate, particularly during the reign of Raja Ahmad. Notable relics such as mosques, tombs, wells, ponds, and bridges serve as physical evidence of this historical period. These artifacts are vital in preserving the historical narrative and educating the younger generation about the Sultanate's legacy. The research underscores the importance of recognizing and safeguarding these remnants for future generations.